THE IMPROVEMENT OF TOURIST-VILLAGE PROMOTION THROUGH THE OPTIMALIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY FOR RURAL-YOUTH - Yogaprasta Adi Nugraha (Research Collaboration Community (RCC), 2020)
Bogor Regency is one of the Jakarta’s buffer cities that able to provide alternative tourism locations for the citizen of the capital and surrounding areas. Ciasmara Village is one of the tourism villages located in Bogor Regency. The main problem encountered by tourism in Ciasmara Village is the lack of promotion and limited infrastructure. These two problems are the biggest factors that hinder the tourism potential of Ciasmara village from being optimally managed. The purpose of this community service activity is to optimize tourism potential through the information and communication technology. Furthermore, the other purpose is to support the behavior shifting of the youth organization in terms of utilizing information and communication technology for the benefit of Ciasmara Tourism village promotion. The method used in this community service activity was discussion and direct training to Ciasmara Village's youth organization. The objective of this community service is Ciasmara Village's youth organization. In the beginning, the target amount of the training participants was at least 20 young people, because there were only 20 active members of the youth organization. In its implementation, this activity was attended by 31-35 participants, indicating that this community service was enticing for Ciasmara village's youths. Through interviews with the head of the youth organizations and the participants, they acknowledged that they were interested in participating in this activity because they felt they had a responsibility to develop village promotions, some of the youth said that they had social media and could promote their area for free. From interviews with several participants and village officials, it was found that this community service activity was able to motivate them to study photography more seriously and utilize social media for the promotion of rural tourism. This can be recognized from the development of official Instagram social media account owned by Ciasmara Village which is indeed focused on promoting tourism and governance in Ciasmara village.